Relation between humoral responses to HIV gag and env proteins at seroconversion and clinical outcome of HIV infection. Issue 6767 (5th January 1991) - Cheingsong-Popov, R; Panagiotidi, C; Bowcock, S; Aronstam, A; Wadsworth, J; Weber, J
Abstract : OBJECTIVE--To study the contribution of the humoral response to HIV-I at seroconversion to disease outcome after 84 months. DESIGN--A retrospective longitudinal study. SETTING--Two haemophilia centres in the United Kingdom. PATIENTS--88 Haemophiliac patients infected with HIV-I for whom sera were available from before seroconversion and in whom clinical follow up data were available. RESULTS--Kaplan-Meier survival analysis showed a significant difference between a high titre (greater than 1600) p24 antibody response at seroconversion and prolonged time before the development of HIV related disease (p = 0.0008). In contrast, higher titres of antibody to gp120 at seroconversion (greater than 25, 600) correlated with more rapid clinical deterioration (p = 0.025). CONCLUSIONS--The first humoral response to HIV proteins at seroconversion is associated with clinical outcome; patients with an initial low titre antibody response to the gagp24 protein have a significantly faster rate of progression to CDC stage IV disease. Patients with a high titre p24 antibody response progress to AIDS more slowly, and these data provide an explanation why p24 antigenaemia is not universally detected in patients with AIDS. It is unclear whether the association between a strong initial p24 antibody response and slower progression of HIV disease is causal and if so whether it is due to viral or host factors.